AB1071 AUTO-IMMUNE AND INFLAMMATORY DISEASES IN CHILDREN WITH SICKLE CELL DISEASE: DIAGNOSTIC AND THERAPEUTIC ISSUES. (June 2019) - Vinit, Caroline; Guitton, Corinne; Benhaim, Patricia; Missud, Florence; Montalembert, Mariane De; Amor, Lahoueri; Arnaud, Cécile; Charara, Oussama; Gajdos, Vincent; Hentgen, Véronique; Kamdem, Annie; Nathanson, Sylvie; et al.
Abstract : Background: Coexistent auto-immune and inflammatory diseases (AIID) and sickle cell disease (SCD) have been recently described in adults and children, however its frequency and physiopathology remain unclear (1–6). Objectives: The aim of this study is the analysis of clinical and biological characteristics at AIID diagnosis and the evolution under treatment in children with SCD Methods: Between May 1991 and March 2018, 35 of 3, 800 SCD children diagnosed with AID in seven hospitals in Paris and suburb were analyzed in a retrospective survey. Results: Thirty-five patients reported 44 AIID: auto-immune liver disease (AILD, n=13), inflammatory bowel disease (IBD, n=7), juvenile idiopathic arthritis (JIA, n=6), systemic lupus erythematosus (n=5), autoimmune hemolytic anemia (n=3), Sjögren's syndrome (n=2), histiocytic necrotizing lymphadenitis (n=2), vasculitis (n=2), myasthenia gravis (n=2), sarcoidosis (n=2), inflammatory uveitis (n=1), sclerodermia/juvenile dermatomyositis (n=1). Median age at diagnosis was 10 [2 – 18] years. The mean delay between first symptom and diagnosis was 15.5 (± 29) months. The time of diagnostic was significantly longer for patients with JIA compared to other AID (63 versus 10 days, p=0.004). Sixteen patients (45.7%) had hypergammaglobulinemia > 20 g/L at diagnosis. AILD had a hypergammaglobulinemia at the time of diagnosis (30.0g/L), with a statically significant decrease at the end of follow-up (18.2g/L, p=0, 0048). Among 21 patients (60%) treated with systemic steroids, it triggered vaso-occlusive crisis in 14 (66.7%), one acute chest syndrome, one transient ischemic attack. Thirteen of 35 patients (37.1%) were managed with biotherapy for AIID, well tolerated. Three patients (8.6%) underwent stem cell transplantation, one died of a cortico-resistant and multipolar graft versus host reaction, two were cured of both AIID and SCD. Nine severe infections were reported, four under steroids, five under biotherapy. Conclusion: Diagnosis and therapeutic care of coexistent auto-immune and inflammatory diseases are difficult and challenging in children with SCD. Annual monitoring of inflammatory markers could be recommended to detect AIID earlier and prevent diagnostic delay in case of high ascension in SCD patients. References: [1] Li-Thiao-Te V, Uettwiller F, Quartier P, et al. Coexistent sickle-cell anemia and autoimmune disease in eight children: pitfalls and challenges. Pediatr Rheumatol Online J. 17 janv 2018;16(1):5. [2] Cherner M, Isenberg D. The overlap of systemic lupus erythematosus and sickle cell disease: report of two cases and a review of the literature. Lupus. juin 2010;19(7):875–83. [3] Adelowo O, Edunjobi AS. Juvenile idiopathic arthritis coexisting with sickle cell disease: two case reports. BMJ Case Rep. 1 déc 2011;2011. [4] Michel M, Habibi A, Godeau B, Bachir D, Lahary A, Galacteros F, et al. Characteristics and outcome of connective tissue diseases in patients with sickle-cell disease: report of 30 cases. Semin Arthritis Rheum. déc 2008;38(3):228–40. [5] Galmiche S, Amiot X, Georgin-Lavialle S, et al. Maladies inflammatoires chroniques de l'intestin chez des patients atteints de syndrome drépanocytaire majeur: à propos de 6 cas. Disponible sur: http://www.em-premium.com.frodon.univ-paris5.fr/article/1122766/resultatrecherche/34 [6] Jitraruch S, Fitzpatrick E, Deheragoda M, et al. Autoimmune Liver Disease in Children with Sickle Cell Disease. J Pediatr. oct 2017;189:79-85.e2. Disclosure of Interests: Caroline Vinit: None declared, Corinne Guitton: None declared, Patricia Benhaim: None declared, Florence Missud: None declared, Mariane De Montalembert: None declared, Lahoueri Amor: None declared, Cécile Arnaud: None declared, Oussama Charara: None declared, Vincent Gajdos: None declared, Véronique Hentgen Consultant for: SOBI, Novartis, Abbvie, Speakers bureau: Novartis, Annie Kamdem: None declared, Sylvie Nathanson: None declared, Brigitte Bader-Meunier: None declared, isabelle melki: None declared, Isabelle Koné-Paut Grant/research support from: SOBI has supported drug product (anakinra) for the presented study, Consultant for: SOBI, Novartis, Pfizer, Abbvie, UCB, CHUGAI, ROCHE, Pierre Quartier Consultant for: AbbVie, Chugai-Roche, lilly, Novartis, Novimmune, Sanofi, and SOBI, Consultant for: AbbVie, Chugai-Roche, Lilly, Novartis, Novimmune, Sanofi, and SOBI, Speakers bureau: AbbVie, BMS, Chugai-Roche, Novartis, Pfizer, and SOBI, Speakers bureau: AbbVie, BMS, Chugai-Roche, Novartis, Pfizer, and SOBI, Loic De Pontual: None declared, Luu-Ly Pham: None declared